Community Language Learning to Improve Students’ Speaking Skill - Eny Gufrina (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
The aim of this research is to find out the improvement of students’ speaking skill by using community language learning. Classroom action research was used to conduct this research with 20 participants of students XII IPS-2 at SMA N 2 Siabu in Academic Year 2019/2020. The data were collected from speaking test, observation and interview in cycle one and cycle two. The indicators of students’ speaking skill are measured from accent, grammar, vocabulary, fluency and comprehension. The result of this research showed that the improvement of mean score of the students’ speaking skill from cycle 1 into cycle 2 was categorized into very good category.